CALIDAD DE VIDA EN RELACIÓN A EXPERIENCIA DE CARIES EN PACIENTES DE LA CLÍNICA ODONTOLÓGICA DE LA UNIVERSIDAD DE SAN MARTÍN DE PORRES DE CHICLAYO. - More-Neyra, Katherine; Rivas-Zavaleta, Carolina; Chumpitaz-Durand, Rubén (Revista Kiru)
Objectives. To determine the relationship between quality of life and caries experience in patients treated at the Dental Clinic of the San Martin de Porres University - Chiclayo Branch, between the months of March and April 2015. Materials and Methods. This study has characteristics of a non-experimental and quantitative study, with descriptive correlational and cross-sectional design. 110 adults patients were evaluated, through the use of stomatology sheets and the quality of life questionnaire WHOQOL - Bref previously validated. The Spearman correlation coefficient to determine the possible association was used. Results. It was determined that 57.27 % of patients with dental caries experience also have moderate quality of life. From the Spearman correlation coefficient was obtained: rho = 0.56 (p < 0.05) which indicates a moderate relationship between quality of life and caries experience. Conclusions. A moderate association between dental caries experience and quality of life was determined in 110 adults patients treated at the Dental Clinic of the San Martin de Porres University – Chiclayo Branch between March and April 2015.